Effect of Losartan on Level of IL-1β Serum in Hypertensive Patients with Asymptomatic Hyperuricemia at Mohammad Hoesin Hospital Palembang. (June 2015) - Imran; Ali, Z.; Ardianto; Mulia, D.P.; Hermansyah
Abstract : Cardiovascular disease is still the leading cause of death in the world. Hypertension and hyperuricemia is known as an important risk factor for cardiovascular disease. The prevalence of hypertension with hyperurcemia between 20–40 %. According NHNES 2007–2008, about74% gouty arthritis patients will suffer hypertension. Hyperuricemia is a condition can cause a systemic inflammation leading to endothelial dysfunction. IL-1β is one of marker systemic inflammation. The aim of this study was to evaluate the administration of losartan 50 mg once daily for 8 weeks on IL-1β serum in hypertensive patients with asymptomatic hyperuricemia This study was before and after design, conducted in Department of Internal Medicine, Mohammad Hoesin Hospital (RSMH) Palembang, began in March-August 2013. Subjects included 30 patients, 53, 3% male and 46, 7% female. The effect of losartan on systolic and diastolic blood pressure (146, 00 ± 4, 98/88, 67 ± 3, 45 mmHg to 126, 67 ± 7, 39/79, 00 ± 4, 02 mmHg, p = 0, 000). The levels of IL-1β serum 0, 99(0, 057–12, 42) pg/ml to 0, 14(0, 057–2, 03) pg/ml and statistically significant different with p < 0, 000 with administration of losartan 50 mg once daily for 8 weeks. This study proved the effect of losartan on the decreased, levels of IL-1β serum.